2021
DOI: 10.1371/journal.pgph.0000026
|View full text |Cite
|
Sign up to set email alerts
|

Health system capacity and readiness for delivery of integrated non-communicable disease services in primary health care: A qualitative analysis of the Ethiopian experience

Abstract: Background Non-communicable diseases (NCDs) now account for about 71% and 32% of all the deaths globally and in Ethiopia. Primary health care (PHC) is a vital instrument to address the ever-increasing burden of NCDs and is the best strategy for delivering integrated and equitable NCD care. We explored the capacity and readiness of Ethiopia’s PHC system to deliver integrated, people-centred NCD services. Methods A qualitative study was conducted in two regions and Federal Ministry of Health, Addis Ababa, Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 26 publications
(41 reference statements)
3
30
0
Order By: Relevance
“…This outcome is consistent with findings from earlier Tanzanian ( Adinan et al, 2019 ), Zambian, and Malawian investigations ( Shiroya et al, 2021 ). The good reason for not providing DM and HPN at the rural health facilities could be improper supportive supervision from the nearby health offices, a little concern for NCDs, and a lack of political commitment ( Tesema et al, 2021 ; Bausch et al, 2021 ; Agunga, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is consistent with findings from earlier Tanzanian ( Adinan et al, 2019 ), Zambian, and Malawian investigations ( Shiroya et al, 2021 ). The good reason for not providing DM and HPN at the rural health facilities could be improper supportive supervision from the nearby health offices, a little concern for NCDs, and a lack of political commitment ( Tesema et al, 2021 ; Bausch et al, 2021 ; Agunga, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our result showed a strong link between HEW performance evaluation practices and NCD prevention services, with delays in conducting assessments having a significant adverse effect on NCD uptake. While a qualitative study in Ethiopia suggests that PHC services receiving greater attention are more likely to be implemented,23 our findings demonstrate complementary effects, as none of the health system factors—such as overall HEW training, supportive supervision, and performance appraisal—captured in our study was explicitly aimed at NCDs.…”
Section: Discussionmentioning
confidence: 67%
“…Previous research BMJ Global Health on Ethiopia's NCD programme at the PHC level indicated that supervisors had minimal knowledge of NCDs while the supervision system itself lacked NCD focus. 23 Such a lack of a deeper understanding of NCD knowledge among supervisors is likely to lead to a greater emphasis on supporting programmes, they were familiar with and trained on; hence the insignificant association with NCD observed in the present study.…”
Section: Bmj Global Healthmentioning
confidence: 61%
See 2 more Smart Citations